The effect of texture and irrigation on the soil moisture vertical-temporal variability in an urban artificial landscape： a case study of Olympic Forest Park in Beijing - Zhang, Xiaofeng; Zhang, Xu; Li, Guanghe (Frontiers of environmental science & engineering, 2015)
Soil moisture variability in natural landscapes has been widely studied; however, less attention has been paid to its variability in the urban landscapes with respect to the possible influence of texture stratification and irrigation management. Therefore, a case study was carried out in the Beijing Olympic Forest Park to continuously monitor the soil in three typical profiles from 26 April to 11 November 2010. The texture stratification significantly affected the vertical distribution of moisture in the non-irrigated profile where moisture was mostly below field capacity. In the profile where irrigation was sufficient to maintain moisture above field capacity, gravity flow led to increased moisture with depth and thus eliminated the influence of texture. In the non-irrigated sites, the upper layer (above 80 cm) exhibited long-term moisture persistence with the time scale approximating the average rainfall interval. However, a coarse-textured layer weakened the influence of rainfall, and a fine-textured layer weakened the influence of evapotranspiration, both of which resulted in random noise-like moisture series in the deeper layers. At the irrigated site, frequent irrigation neutralized the influence of evapotranspiration in the upper layer (above 60 cm) and overshadowed the influence of rainfall in the deeper layer. As a result, the moisture level in the upper layer also behaved as a random noise-like series; whereas due to deep transpiration, the moisture of the deep layer had a persistence time-scale longer than a month, consistent with characteristic time-scales found for deep transpiration.